DESIGN THINKING WITH INFORMATION TECHNOLOGY SUPPORT AS A SOLUTION TO THE PROBLEM OF CSR SOEs IN INDONESIA - Rozahi Istambul , Muhammad; Abinowi, Egi (International Journal of Psychosocial Rehabilitation, 2020)
State-owned enterprises (SOEs) in Indonesia are non-profit companies managed by the state that will help the community, including small and medium enterprises (SMEs) in running their business through capital loans to develop the production processes run by the SMEs concerned. The capital from these SOEs comes from the Corporate Social Responsibility (CSR) of each company in SOEs and has a division that will help provide soft loans, known as the Partnership and Community Development Program (PKBL). However, in the process, SMEs need policy procedures established by PKBL to channel soft loans (capital) according to applicable criteria, if SMEs can make a complete and good business proposal then PKBL will then follow up on that capital. The problem is that many SMEs do not know and find it difficult to make business submission related to their businesses, whereas, on the other hand, many SMEs have the opportunity to repeatedly capitalize on different SOE companies because they can make a good business submission. This problem requires PKBL to manage business processes more optimally by distributing loans equally and fairly to different SMEs. This problem solving was made using the design thinking method approach that involved all PKBL parties so that they could coordinate optimally. While the implementation action process involves the role of information technology developers.